Anomalous Appearance of a Distinct Glass Transition in Perfluoroimide Acid Ionomers. (3rd July 2019) - Orsino, Christina Marie; Lindell, Matthew; Yandrasits, Michael; Hamrock, Steven; Moore, Robert B
Abstract : This work presents the first in-depth study on the thermal and dynamic mechanical properties of multi-acid perfluorinated ionomers developed by 3M. Perfluoroimide acid ionomer (PFIA) contains two acidic sites per sidechain as opposed to conventional perfluorosulfonic acid ionomers (PFSA) with only one. This additional acidic site leads to remarkable improvements in proton conductivity and presents a novel membrane for use as proton exchange membranes in fuel cells. Interestingly, the additional acidic site on PFIA leads to unexpected differences in thermal and mechanical properties, including the appearance of a distinct glass transition temperature otherwise not seen in PFSA ionomers. Here we probe the apparent glass transition and assign it to the true glass transition temperature of PFIA.